THE INTEGRATION OF SHARIA-BASED GOOD CORPORATE GOVERNANCE AND ENVIRONMENTAL, SOCIAL, AND GOVERNANCE IN ENHANCING DONOR PARTICIPATION - Eko Muliansyah; Marko S Hermawan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study examines the influence of Good Corporate Governance based on the Sharia Enterprise Theory on donor participation at LAZNAS Baitul Maal Hidayatullah Central Jakarta. It was conducted with Environmental, Social, and Governance serving as a moderating variable. Effective governance is considered essential for enhancing accountability, transparency, independence, responsibility, and fairness in zakat management. The study aims to fill a gap in the existing literature by investigating how these GCG components shape donor engagement. Using a quantitative research design, the study surveyed 322 active zakat donors selected through the Slovin formula. Statistical analyses were applied to assess both the direct and indirect effects of GCG components on donor participation. The findings indicate that accountability and transparency exert significant positive effects on donor participation, both directly and indirectly through ESG mediation. In contrast, responsibility and independence do not show significant direct effects but do demonstrate meaningful indirect influences via ESG. Furthermore, fairness exhibits both direct and indirect significant impacts on donor participation. These results highlight that integrating Sharia-based GCG with ESG principles effectively strengthens donor trust and loyalty. The study recommends reinforcing transparency, implementing rigorous auditing practices, and adopting comprehensive ESG strategies to ensure sustainable, efficient, and socially responsible zakat governance.